(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the first years after the war, the situation of the light and food industry in the southern regions of Uzbekistan the reconstruction of existing enterprises and the establishment of new industrial enterprises, it is mainly about the industrial enterprises established after the Second World War. Also, the practice of equipping industrial premises with modern equipment and technology, the role of rationalization and inventiveness in industrial development, the reduction of working hours of light industry employees, the improvement of labor productivity and the production of quality light industry products were mentioned. historical description of the causes, problems and consequences of the economic backwardness of the southern regions during the years of Soviet power, and the factors that hindered the development of the light and fast food industry during the years of stagnation.